Respuesta :

[tex]k^2-8k+20=8[/tex][tex]k^2-8k+12=0[/tex][tex]k^2-8k=-12[/tex][tex]k^2-8k+16=-12+16[/tex][tex](k-4)^2=4[/tex]

then k-4=2 or k-4=-2

and we have that k=6 and k=2, are the two answers for the equation.

if we replace k=2 in the first equation

[tex](2)^2-8(2)+20=4-16+20=-12+20=8[/tex]

which makes the equation true for k=2, then is we replace k=6 in the first equation:

[tex](6)^2-8(6)+20=36-48+20=-12+20=8[/tex]

then the equation holds for k=6 too.

the second equation is:

[tex]2=\sqrt[]{-4-x}[/tex]

then

[tex]4=-4-x[/tex][tex]x=-4-4[/tex]

finally

[tex]x=-8[/tex]

if we replace x=-8 in the second equation

[tex]\sqrt[]{-4-(-8)}=\sqrt[]{-4+8}=\sqrt[]{4}=2[/tex]

then the equation holds for x=-8.